BCLI GENE POLYMORPHISM OF GLUCOCORTICOID RECEPTOR IN CHILDREN WITH BRONCHIAL ASTHMA - M.V. Zhdanova (Педиатрическая фармакология, 2006)
Airways inflammation and immune activation are known to play an important part in asthma patogenesis. Glucocorticoids are commonly used as the most effective agents to treat asthma. frequency in alleles and b cligene polymorphism of clucorticoid receptor has been studied in children with mild to severe asthma and in controls. The alleles and b cligene polymorphism genotypes have been uniformly distributed in all groups regardless to asthma severity. Distribution corresponds with the data obtained in the western countries.Key words: bronchial asthma, glucocorticoids, glucocoticoid receptor, glucocoticoid receptor gene, bcli polymorphism, children.